Agroclimate Information Systems (ACIS) for women and ethnic minority farmers in Southeast Asia - Simelton, Elisabeth (World Agroforestry Centre, 2019)
Presented by Elisabeth Simelton (World Agroforestry Center) on January 23, 2019 as part of the webinar 'Guidelines and good practices for achieving gender equality outcomes through climate services'. The webinar was co-organized by the CGIAR Collaborative Platform for Gender Research and the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS).